(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
India has growth prospect for finance industry with a huge number of consumers and other favorable factors. Opposition to liberalizing FDI in this sector raises concerns about employment losses, unfair competition resulting in large-scale exit of incumbent domestic finance and infant industry arguments to protect the organized domestic finance sector that is at a nascent stage.In 2012 the Indian Government approved proposal of 100 percent FDI in finance in India subject to certain conditions. Though this proposal is being hailed by global finance giants, which until now have been involved in only wholesale cash and carry distribution in India and have been longing for entry into the Indian finance market for years. The proposal has received vehement opposition from a spectrum of political parties in India, many of them urging for a reversal of the proposal. As a result, the Indian government has stalled the implementation of this proposal which has temporarily washed off the wishes of the global finance players awaiting a bite of the Indian finance market. This paper attempts to study the present status of FDI in finance sector in India and the impacts of FDI on various concerned segments.